Mission critical - Gannon, Charles E.; Barber, Griffin; Kennedy, Chris, 1965-; Massa, Mike, 1967- (Gannon, Charles E. Tales of the Terran Republic., 2024)
"Major Rodger Y. Murphy should have died when his helicopter crashed off the coast of Mogadishu in 1993. Instead, he woke up in 2125, 152 light-years from home. Murphy and 100 other "Lost Soldiers" have been retrieved and awakened by two officers of the Consolidated Terran Republic: Trevor Corcoran and Richard Downing. Promising to return, Corcoran and Downing leave the twentieth-century castaways with a daunting objective: establish a base of operations on the main world of R'Bak using local allies they have yet to recruit and enemy equipment they have yet to seize. They haven't been back yet. But the company of misfits and ne'er-do-wells who've taken the nickname Murphy's Lawless rise to the challenge!"--